Differences in the Lateral Range of Motion of the Cervical Spine Between Young and Elderly Adults - Anna Cláudia Freire de Araújo Patrício; Karoline de Lima Alves; Jiovana de Souza Santos; Daniele Ferreira Rodrigues; Teresa Cristina Rosa Romero Navarine; Michelle Salles de Oliveira (Universidade Federal de Santa Maria, 2014)
Doi: 10.5902/2179769211310 Aims: to analyze the differences in the lateral range of motion of the cervical spine, among young and elderly people. Method: a quantitative and comparative study carried out in João Pessoa/Paraiba, with 55 elderly people and 55 young people. A flexibility test of the cervical spine was held, and the goniometer Sanny® was employed. It was considered p<0.05. Results: the elderly were 68 ± 6 years old and the young 23 ± 3 years old, and they showed 20.4 ± 6.4 degrees and 31 ± 7 degrees of right range of motion, respectively. Regarding the left side, the elderly reached 29 ± 7 degrees and the young 32 ± 6 degrees; both sides with p<0.05. Conclusions: it was observed that the participants showed lower range of motion, compared to the range established in the literature. It is necessary to develop methods that evaluate individuals in order to detect limited range of motion of the cervical spine early on.